The Mexican Financial Crisis : A Test of the Resilience of the Markets for Developing Country Securities - Ishii, Shogo (IMF Working Papers; Working Paper, 1995)
This paper reviews developments in private capital flows to developing countries since the Mexican financial crisis in December 1994. The paper points out that a strong recovery in these flows masks some significant changes in their characteristics, particularly in the type of borrowers back toward sovereigns and the currency denomination of new issues shifted away from U.S. dollars. Terms of new bond issues became significantly less favorable than before the Mexican crisis. One of the most striking developments was the sharp increase in bond placements by developing countries in deutsche mark and yen. It is shown that relatively favorable credit ratings assigned by Japanese rating agencies facilitated some developing countries to tap the yen bond market.